CLASSICAL MIGRAINE - Shahdevi Nandar Kurniawan; Dyah Kusuma Wardhani (Journal of Pain, Headache and Vertigo, 2022)
A classic migraine is a recurrent attack of visual, sensory, or other central nervous system symptoms that are unilateral and last several minutes, followed or not followed by a migraine attack. Migraine commonly occurs in 19% of women and 11% of men worldwide, with 20% of sufferers experiencing classic migraine. The etiopathophysiology of classical migraine is not known with certainty, but vascular, neurological, and genetic dysfunction are suspected to be the cause. Classical migraine pathophysiology is associated with the theory of cortical spreading depression, which can explain the process of aura. There are four phases in classical migraine, namely prodromal, aura, headache, and prodromal phases, each of which has its own symptoms. This is the basis for the diagnosis of migraine, which is established based on the history and physical examination. Migraine therapy includes preventive therapy (lifestyle changes and prophylactic administration) as well as abortive therapy (administration of specific and non-specific drugs).